PERILAKU PENGENDARA SEPEDA MOTOR RODA DUA DI KOTA BANGKINANG KABUPATEN KAMPAR - Shatika Azira; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The lack of order and compliance of motorcycle riders caused many traffic violations. Starting from violations of road markings, traffic signs, breaking into APILLs and other violations become things that can be seen every day. Of course this is influenced by various factors. This study aims to find out what factors influence traffic violations and how the relationship between education, employment and income to the level of violations of traffic rules. This research is a inferensial quantitative study, by using a nonprobability sampling technique and the research sample is determined by using quota and incidental technique. Respondents in this study is 50 motorbike riders in the Bangkinang city. Data in this study were taken using a questionnaire. Questionnaire data in the form of ordinal data and analyzed using descriptive statistics, crosstabulation, and Spearman rank nonparametric statistical tests, to see the relationship between education, employment and income to the level of traffic violations. then to look at factors of violation of data traffic taken with a questionnaire with descriptive analysis. This study found a relationship between education and the level of violations negatively correlated, which means higher levels of education tend to have low levels of violations. Between the level of violation and occupation has a negative correlation which means that respondents who have good jobs tend to commit fewer violations. Whereas the relationship between income and the level of violation is negatively correlated. respondents with high incomes commit fewer traffic violations. While the factors that drive the level of traffic violations are influenced by Indiscipline factor (indiscipline factor), Ignorance / forget factor, Ignorance factor (ignorance factor), Negligence factor, and Road infrastructure facilities. The highest factor affecting traffic violations in the city is negligence of motorcycle riders.Keywords: Abuse, Motorcycle, Traffic